Vertebral Compression Fractures: Evaluation and Management - Madassery, Sreekumar (Seminars in Interventional Radiology, 2020)
Painful vertebral body compression fractures are prevalent in elderly patients. Two-thirds of patients will have spontaneous resolution of pain in 4 to 6 weeks and initial management is nonoperative with pain management and bracing. A focused history and exam can identify patients likely to benefit from vertebral body augmentation (e.g., vertebroplasty or kyphoplasty). Patients with persistent back pain and bone marrow edema on magnetic resonance imaging may benefit from injection of cement into the fractured vertebral body with either vertebroplasty or kyphoplasty. Patients most likely to benefit are those with severe pain refractory to nonoperative management who are offered intervention within 3 weeks. The procedure is usually performed as an outpatient with rare complications. Most patients report immediate, durable pain relief.
Keywords: osteoporosis; vertebral compression fracture; vertebral body augmentation; kyphoplasty; vertebroplasty; interventional radiology